Inovasi Pencegahan Stunting Dalam Menggunakan Aplikasi Elsimil - azkia, milati; Indriyanti, Mila; Eko Ginanjar, Sunandie; Santa, Rahmat; Maryulina, Teti (LPPM STIA Lancang Kuning Dumai, 2024)
The role of BKKBN in preventing stunting through the ELSIMIL application program (Electronic Ready to Marry and Ready to Get Pregnant) in Gumuruh village Marriage and reproductive health are important aspects of people's lives. The research method uses qualitative methods (Sugoyono. 2022). Respondents in this study were all prospective brides in Gumuruh Village, totaling 19 pairs of prospective brides. To find out the role of the Population Control and Family Planning Office, Women's Empowerment and Child Protection in reducing stunting rates through Bina Keluarga Balita (BKB), researchers use information collection techniques using observation, interviews, and documentation studies. The ELSIMIL application has important features that can be used by users and assistants in anticipating stunting in prospective brides. In today's advanced period, information and communication technology has become a fundamentally part of everyday life. Portable health applications have become an effective means of providing health information, education, and support to individuals. The application developed by the National Population and Family Planning Agency (BKKBN) is the Elsimil (Electronic Ready for Marriage and Pregnancy) application, which aims to improve the knowledge and reproductive health of prospectiv e brides (BKKBN, 2021). Keywords: Innovation, Elsimil, Service, Stunting